2020
DOI: 10.1371/journal.pone.0218767
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differentials in hypertension based on JNC7 and ACC/AHA 2017 guidelines mediated by body mass index: Evidence from Nepal demographic and health survey

Abstract: Background Unlike developed countries, higher socioeconomic status (SES-education, and wealth) is associated with hypertension in low and middle-income countries (LMICs) with limited evidence. We examined the associations between SES and hypertension in Nepal and the extent to which these associations vary by sex and urbanity. The body mass index (BMI) was examined as a secondary outcome and assessed as a potential mediator. Materials and methods We analyzed the latest Nepal Demographic and Health Survey data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
2
15
1
Order By: Relevance
“…We found that the likelihoods of hypertension awareness and treatment increased with increasing wealth quintiles for which there is inconclusive evidence in the literature 33 , 34 ; however, we did not find differences in hypertension and its control across wealth quintiles. It may suggest that a similar rising pattern of hypertension in all segments of population is observed regardless of their wealth quintiles; however, people with improved socio‐economic status are more likely to be aware of their conditions and received treatment.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…We found that the likelihoods of hypertension awareness and treatment increased with increasing wealth quintiles for which there is inconclusive evidence in the literature 33 , 34 ; however, we did not find differences in hypertension and its control across wealth quintiles. It may suggest that a similar rising pattern of hypertension in all segments of population is observed regardless of their wealth quintiles; however, people with improved socio‐economic status are more likely to be aware of their conditions and received treatment.…”
Section: Discussioncontrasting
confidence: 87%
“…However, people from higher socio‐economic status are more likely to consume more energy, and involved in white‐collar jobs and follow sedentary lifestyles, which may increase the risk of high BP. 34 In contrast, several studies, including meta‐analyses, suggest a higher prevalence of hypertension in lower socioeconomic groups in HICs due to their higher smoking rates, elevated BMI, and lack of exercise than higher socio‐economic groups. 33 , 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…The largest inequality gap was seen in arthropathies and hypertension/high cholesterol, mainly due to higher prevalence rates in low SES groups. Low SES is indeed found to be associated with the risk of developing arthritis and hypertension due to higher smoking rates, body mass index (BMI), and lack of exercise compared to high SES groups [30][31][32] . There is also strong evidence that SES is associated with worse HRQoL outcomes 25,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Results were presented as adjusted odds ratio (aOR) and 95% confidence interval (CI). All analyses accounted for complex survey design to adjust clustering variation, the probability of selection, and non-response in the NDHS [32]. All statistical tests were two-sided, and a p-value < 0.05 was the level of significance.…”
Section: Discussionmentioning
confidence: 99%